Evolution of diagnostic criteria for diabetes - Davidson, Mayer (Henry Stewart Talks, 2013)
Description & symptoms of diabetes, Criteria for screening and challenges, Abbreviated history of diabetes diagnosis, Glucose distribution (unimodal & bimodal), Cutoff values & mathematical manipulations, Different criteria for diagnosis of diabetes & diabetes classifications, WHO criteria for diabetes mellitus, Relationship between FPG & 2hr value on OGTT, Decisions of the expert committee – Glycation, The Pima Indians, Egyptian, and NHANES III studies, Prevalence of retinopathy, Oral glucose tolerance tests, Quantitation of variation, Using HbA1c levels to diagnose diabetes, Expert committee on diagnosis of diabetes, Screening for diabetes before and after 2010 ADA criteria and recommendations for diabetes diagnosis
Reviewed at 2021/09/30